1982
DOI: 10.1021/bi00535a017
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of microtubule protein: role of guanosine di- and triphosphate nucleotides

Abstract: A quantitative analysis of the interplay between guanosine 5'-triphosphate (GTP) and guanosine 5'-diphosphate (GDP) in microtubule assembly and accompanying GTP hydrolysis has been performed when tubulin was polymerized in the presence of microtubule-associated proteins (MAPs) which display an interfering GTPase activity. The use of adenylyl beta-imidodiphosphate, which specifically inhibits the MAPs GTPase activity, and of vinblastine (or podophyllotoxin), which specifically inhibits GTP hydrolysis due to tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 30 publications
(42 reference statements)
2
52
0
Order By: Relevance
“…Previous experiments (18) have indicated that this ratio is close to zero because tubulin does not bind to a GDP-bound end.…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous experiments (18) have indicated that this ratio is close to zero because tubulin does not bind to a GDP-bound end.…”
Section: Methodsmentioning
confidence: 76%
“…These data (18) suggest that not only is GTP hydrolysis not necessary for polymerization but it inhibits polymerization. It is likely that the rate of dissociation of tubulin subunits also depends on whether GTP or GDP is bound at MT ends.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In such a system at steady state, a net growth at one end is compensated by a net dissociation at the opposite end. The efficiency of this treadmilling depends on the nucleotide composition of at least one end [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…20,21) These facts mean that tubulin and the tubulin-colchicine complex have GTPase activity. 22,23) The GTPase rate is not in proportion to the rate of microtubule assembly and polymerization, 21,22,24) while the hydrolysis occurs at microtubule ends. 24) The addition of GDP to the microtubule assembly system induces the inhibition of the reaction.…”
mentioning
confidence: 99%